The Influence of Motivation, Self-Confidence and Maximum Oxygen Consumption on Skills Basic Soccer Game - Syahruddin Syahruddin; M. Sahib Saleh; Muhammad Syahrul Saleh; Adhie Mahdhi Iriansa (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of motivation, self-confidence, and maximum oxygen consumption on the basic skills of playing soccer. This research includes path analysis research (path analysis). Exogenous variables are motivation (x1), confidence (x2), and maximum oxygen consumption (x3), while endogenous variables are the basic skills of playing soccer. The sample of this research was 100 male students of class XI MAN 2 Bone. Data were analyzed by inferential statistical analysis, namely the regression test. The findings showed that motivation (MTV), self-confidence (PD), and maximum oxygen ability (VO2 max) affected the basic skills of playing soccer (KSB) (p<0.05). This study only involved a small sample, so the findings of this study can still be developed for further research using more methods or samples.